Elevated bacterial endospores associated with thermogenic hydrocarbon seeps in deep sea sediments. (March 2023) - Rattray, Jayne E.; Elizondo, Gretta; Sloan, Kathryn; Morrison, Natasha; Fowler, Martin; Gittins, Daniel A.; Webb, Jamie; Calvin Campbell, D.; MacDonald, Adam; Hubert, Casey R.J.
Highlights: Significantly higher abundances of endospores at deep sea hydrocarbon seep sites. DPA proxy presents utility for investigating historical seep sites. Archived deep biosphere cores are suitable for endospore analysis for increased understanding of hydrocarbon seeps. Relationship between DPA and alkylnaphthalenes suggests link between deep biosphere hydrocarbon biodegradation and endospore formation. Abstract: Endospore distributions in marine sediments are influenced by geological conduits providing routes for subsurface to surface microbial dispersal. To examine this phenomenon in more detail, endospore abundance was determined by quantifying dipicolinic acid (DPA) in 16 deep sea sediment cores from hydrocarbon prospective areas in the NW Atlantic Ocean. DPA concentrations were compared with measurements of over 250 different gaseous and liquid hydrocarbon compounds used to assess for the presence of thermogenic hydrocarbons. This revealed significantly higher levels of endospores at hydrocarbon seep sites than at most hydrocarbon-negative sites. In one exceptional case, a hydrocarbon-negative core in close proximity to adjacent thermogenic seep sites exhibited high endospore abundance, indicating either deposition of endospores emitted from the subsurface via nearby seepage, or alternatively a historical thermogenic hydrocarbon seep where hydrocarbons can no longer be detected by standard geochemistry approaches. This work expands the application of DPA as a proxy for quantifying dormant endospore biogeography of both recent and paleoenvironmental hydrocarbon seep sites.